Еffects of sectoral structure of foreign direct investment on economic development: the case of Еuropean developing countries - Despotović, Danijela; Dimitrijević, Miloš; Savićević, Marko (Serbian Journal of Management, 2024)
The inflow of foreign capital from multinational companies from all over the world, in the form of foreign direct investments (FDI), intensified economic dynamics and contributed to the improvement of macroeconomic performance. In certain economic sectors and activities, FDI has become the carrier of economic growth, encouraged by intensive processes of deindustrialization and reindustrialization. Namely, FDI can have both positive and negative impact on economic growth and development. This depends on the ability of the economic sectors to overcome the negative effects of FDI in a certain period of time, which can only be achieved if the sectors are export-oriented and introduce new technologies into their operations, thereby increasing productivity and competitiveness. Ordinary Least Squares (OLS) panel regression showed this was not the case in the primary and secondary sectors in the countries of Central and Eastern Europe (CEE) and the Western Balkans (WBs), which are still predominantly labor-intensive and therefore have a negative impact on economic development. As opposed to the agricultural and industrial sectors, the services, under the influence of technological progress, is profiled as a capital-intensive sector with a statistically significant positive impact on economic growth and development.
Keywords: CEE; competitiveness; economic development; FDI; sectoral structure; WBs